Rapid extraction of total RNA from an anaerobic sludge biocoenosis - Rittmann, Simon; Holubar, Peter (Folia microbiologica, 2014)
In order to assess the activity of metabolic pathways during anaerobic biogas production, it is necessary to isolate total RNA from the anaerobic sludge. mRNA activity profiling complements the quantification of excreted metabolites for a comprehensive anaerobic digestion model (ADM1). Four non-commercial total RNA extraction protocols were examined to extract total RNA from suspended solids of anaerobic sludge. The most suitable protocol was identified and optimised. In relation to total RNA extraction efficiency, total RNA purity and RNA integrity, the best homogenisation method was a combined method of nitrogen grinding and bead beating. When bead beating or nitrogen grinding was used alone for homogenisation, total RNA extraction efficiency was lower than when both homogenisation methods were applied. Depending on the homogenisation method, the whole RNA extraction procedure takes approximately 2 to 3 h, which is as fast as when using commercial available soil RNA extraction kits. The proposed method is rapid in extracting total RNA from a biocoenosis present in an anaerobic sludge environment. Furthermore, we could apply any of the extracted homogenization methods for reverse transcription and subsequent PCR amplification of the gene for the methyl coenzyme M reductase alpha subunit (mcrA/mrtA).
Keywords: Microbiological Techniques; RNA; molekulární biologie; časové faktory; odběr biologického vzorku; Sewage; Anaerobiosis; Specimen Handling; Time Factors; mikrobiologické techniky; odpadní vody; Molecular Biology; anaerobióza